PRELIMINARY CHAMBER, A NEW INSTITUTION IN THE ROMANIAN PROCEDURE LAW - Alexandru MARIAN (Challenges of the Knowledge Society)
The Prosecutor, in charge with the criminal prosecution, informs the Court through the indictment drawn up by him. Given its importance, as Court informing document, the law provides special treatment for its content and form. Both the end of the criminal prosecution and the arraignment, as distinct moments of the procedure, are parts of the criminal prosecution, considered criminal trial phase. The New Criminal Procedure Code introduced this new phase, the preliminary chamber, with the purpose to verify the lawfulness of arraignment. Thus, incorrectly drawn up files are stopped from being presented before the Court.